Clinical features of sarcoidosis patients presenting with head and neck manifestations – a two-center retrospective study and proposal of a diagnostic algorithm for the otorhinolaryngologist. (1st February 2020) - Send, Thorsten; Korsten, Peter; Bertlich, Mattis; Braunwarth, Christoph; Bootz, Friedrich; Skowasch, Dirk; Jakob, Mark
Abstract: Background and Aims: We aimed to investigate the clinical characteristics of patients presenting with sarcoidosis of the head and neck as the initial manifestation and to provide recommendations for the diagnostic work-up for the practicing otorhinolaryngologist. Material and Methods: We performed a retrospective cohort study at two university medical centers in Germany. Patients with a histopathologically confirmed diagnosis of sarcoidosis treated in the otorhinolaryngology departments were analyzed. Results: We identified 62 patients (2003–2016). In total, 85.4% ( n = 53) of patients received the initial diagnosis of sarcoidosis during their ENT treatment. Sarcoidosis was detected in the lymph nodes in 42.3% ( n = 30) of the patients; 57.7% had extra-lymphatic manifestations. Fifteen patients (24.2%) showed pulmonary involvement. 30.6% ( n = 19) were treated with oral glucocorticoids (GC) alone, three patients with GC and methotrexate, one patient initially received a combination of GC and azathioprine, one patient rejected the recommended treatment. Conclusions: Sarcoidosis should be considered as a differential diagnosis in patients presenting with head and neck symptoms. The most frequent presenting symptoms were cervical lymphadenopathy and affection of the paranasal sinuses. Therefore, otorhinolaryngologists should be aware of sarcoidosis and help guide referral strategies as they may be the first physicians treating these patients.